KADAR DAN SEBARAN PENCEMARAN MERKURI (Hg) AKIBAT PENAMBANGAN EMAS RAKYAT DI LOKASI HUTAN KERANGAS KECAMATA MANDOR KABUPATEN LANDAK - anto, Feri; hanuddin, Bur; Widiastuti, Tri (JURNAL HUTAN LESTARI, 2013)
Forest kerangas ( heath forest) representing one of important forest type in indonesia which grow above land of podsol, sand kuarsa which den, impecunious of low hara and pH 3-4 ( acid). sensitive and harsh tekstur land ground to trouble. type of vegetasi of forest kerangas own the slimmer manner vegetasi, tree closeness seldom, and apart between one tree with the wide the other tree. Merkuri and compound clan, as does with the metal etc, gone the round of in nature, start from rock, irrigate even at atmosphere coat. at rock, merkuri found by as part of cinnabar mineral ( HgS), in territorial water environment, merkuri stay in the form of ion of metal organic of like metal of merkuri, while in atmosphere, merkuri found in the form of free metal like Hg2+ and Hg0 and berikatan with compound. Rate merkuri of at Farm ofis ex gold mine old age 4-5 year of equal to 0,020 ppm, at farm ofis ex gold mine old age 6-10 year of equal to 0,0502 ppm and at farm ofis ex gold mine old age 11-15 year of equal to 0,042 with the mean rate of equal to 0,037 ppm. Mean of swampy forest of horizontal merkuri of at research location ofis ex- mining with the distance 100 m from river is 0,034 ppm, apart 300 m from river of equal to 0,041 ppm and apart 100 m from river of equal to 0,036 ppm with the pattern of swampy forest which still have the character of local. Vertical swampy forest mean of merkuri of at research location ofis ex- mining with the deepness 19-21 cm is 0,040 ppm and deepness 39-41 cm is 0,034 ppm. Mean of swampy forest of merkuri of according to gratuity of closing vegetasi of at research location ofis ex- mining with the gratuity of closing vegetasi 0-30% is 0,040 ppm, gratuity of closing vegetasi 31-60% is 0,040 ppm and gratuity of closing vegetasi > 61% is 0,031 ppm. Keyword : Contamination Merkuri, Gold Mine People, Forest Kerangas